Capturing meso-level synchronisation tendencies in elite football teams: A novel method for analysing collective organisation in performance - Santos, R.; Garganta, J.; Lopes, R. J.; Davids, K.; Ribeiro, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology)
This study explores emergent synchronisation tendencies in elite football teams, emphasising how players coordinate their collective actions in sub-phases of play to achieve performance goals under various competitive constraints. Drawing on ecological dynamics, the study highlights the player-environment relationship, analysing how ecological variables, such as field position, goal targets, and locations of teammates and opponents, shape collective decision-making. A novel method, using a newly developed coordinate system for capturing meso-level synchronisation tendencies is introduced, defined by values of angle and distance of subgroups of players (simplices) to the goal. This approach is designed to capture the continuous adaptive needs of homeostatic regulation in performance, successfully observing and reporting synchronisation tendencies between players that emerge at the meso-level scale. Results demonstrated greater system sensitivity in detecting synchronisation tendencies between players, compared to traditional coordination analysis methods. The key performance variables, angle and distance to goal, are critical constraints on players’ synchronised behaviours during competitive performance. This novel method for observing and reporting synchronisation tendencies can provide team sports coaches with crucial information to effectively structure and monitor player transactions during performance and training sessions.